A Laboratory Test on the Vibration Mitigation Efficiency of Floating Ladder Tracks. (2017) - Ma, Meng; Jiang, Bolong; Li, Minghang; Sun, Xiaojing
Abstract: With the rapid development of railway systems, increasingly more environmental concerns are focused on railway vibrations. The track solution with the mass-spring-damping principle can be the most effective and economical option to control train-induced ground vibrations. The effect of track vibration mitigation is usually described by insertion loss (IL). IL can typically be obtained by impulse tests in laboratories. To investigate the influences of preloads on IL, a dynamic laboratory experiment was performed on a floating ladder track. Two conditions were considered, a ladder sleeper with and without under sleeper pads (USPs). A modal test was performed, and then, an automatic falling weight system was used for the vibration reduction test. A preloaded car with a deadweight of 2.4 tons was employed. Different concrete masses, with a maximum of 5.4 tons of total weight were applied on the car. Ground vibrations and IL were analysed under these different preloaded weights. The results show that the first natural frequency of the floating ladder track was 33 Hz. When the preload was applied, the ground vibration and IL around the natural frequency were largely influenced. In addition, the values of IL in different frequencies had different sensitivities to the preloads.